2020
DOI: 10.26434/chemrxiv.11691714.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering High Energy Density Sodium Battery Anodes for Improved Cycling with Superconcentrated Ionic Liquid Electrolytes

Abstract: <div> <div> <div> <p>Non-uniform metal deposition and dendrite formation in high density energy storage devices reduces the efficiency, safety, and life of batteries with metal anodes. Superconcentrated ionic liquid (IL) electrolytes (e.g. 1:1 IL:alkali ion) coupled with anode preconditioning at more negative potentials can completely mitigate these issues, and therefore revolutionize high density energy storage devices. However, the mechanisms by which very high salt concen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
(61 reference statements)
2
2
0
Order By: Relevance
“…The Au (111)|50 mol% LiFSI in P1222FSI interface was examined without applied bias and at -3.7, -8.6, and -14.4 μC/cm 2 . As shown in Figure 5a, the overall number of interfacial layers detected for the examined system was found to be around 2-3 regardless of the surface charge, similar to observations for super-concentrated NaFSI and LiFSI in pyrrolidinium FSI IL systems [46,47]. The innermost layer was defined within a distance of 0.61 nm from the Au (111)…”
supporting
confidence: 80%
See 3 more Smart Citations
“…The Au (111)|50 mol% LiFSI in P1222FSI interface was examined without applied bias and at -3.7, -8.6, and -14.4 μC/cm 2 . As shown in Figure 5a, the overall number of interfacial layers detected for the examined system was found to be around 2-3 regardless of the surface charge, similar to observations for super-concentrated NaFSI and LiFSI in pyrrolidinium FSI IL systems [46,47]. The innermost layer was defined within a distance of 0.61 nm from the Au (111)…”
supporting
confidence: 80%
“…The number of anions coordinating with one Li + is barely affected, whereas that of OFSI shows a decrease from ~ 4.5 to ~ 3.0 (Figure 5e), which also consistently responds to the change in the FSI/Li ratio. These observations were also found for LiFSI and NaFSI systems in pyrrolidinium FSI electrolytes, which implies that the trend in Li(Na)-FSI coordination changes upon applied bias, under the conditions given here for a Au metallic substrate, is more affected by salt concentration and additives than by the nature of the IL cation [46,47]. Molecular orbital energy analysis showed that these Li-FSI coordination changes affect both HOMO and LUMO levels [46], which suggests that the [Li(FSI)3] -2 unit is reductively unstable upon charging to -14.4…”
supporting
confidence: 72%
See 2 more Smart Citations